CONNOTATIVE MEANING IN SELECTED SONGS “ME & MR. JONES; REHAB; BACK TO BLACK” FROM BACK TO BLACK ALBUM OF AMY WINEHOUSE - Putri Adelia; Rulik Setiani (JETAL: Journal of English Teaching & Applied Linguistic, 2026)
Song lyrics often convey meanings beyond their literal sense, making connotative meaning an important focus in semantic analysis. However, studies examining connotative meaning in selected songs from Amy Winehouse’s Back to Black album remain limited. This study therefore aims to identify and classify the connotative meanings found in Me & Mr. Jones, Rehab, and Back to Black. Using a descriptive qualitative method, the data consisted of song lyrics collected through documentation and note-taking techniques and were analyzed using Geoffrey Leech’s concept of connotative meaning and Abdul Chaer’s classification of positive, negative, and neutral connotations. The results show a total of 36 connotative meanings, consisting of 6 positive, 23 negative, and 7 neutral, indicating a clear dominance of negative connotation. The dominant negative connotations reflect themes of betrayal, heartbreak, addiction, emotional conflict, and psychological struggle, while positive and neutral connotations appear less frequently to support the emotional and contextual meanings of the lyrics. This numerical pattern demonstrates that connotative meaning plays a significant role in expressing emotional experiences and enriching the interpretation of song lyrics beyond their literal meanings.